The Influences of Bondol Attack Against Paddy Damage in Bogor - Arseki Ardjansyah; Jarwadi Budi Hernowo; Swastiko Priambodo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Bondol bird group known as one of the pests that attack paddy. This study aims to identify the number of individuals, attack frequency, damageto paddy and control efforts of bondol groups. There were three types of bondol groups, they were 256 scaly-breasted munia (Lonchura punctulata),1.075 javan munia (L. leucogastroides) and 94 white-headed munia (L. Maja). There were 1.090 bondol recorded in Sawah Baru and 335 inCiherang. At morning became the most frequent time to bondol in attacking paddy, as many as 97 times in Sawah Baru and 37 times in Ciherang. Thenumber of damage paddy in Sawah Baru during the observation amounted 4,24%. The number of damage paddy in Ciherang during the observationamounted 4,05%. Losses suffered by farmers during the observation as much as IDR 2.500.325 million/ha in Sawah Baru and IDR 1.064.040million/ha in Ciherang. Bondol bird control effort to tackle it's attack only performed in Sawah Baru, which is shaking bambo tied with plastic andshout to chase away bondol.Keywords: bondol bird, Ciherang, paddy, Sawah Baru